A Study of the Use and Usability of an LMS (RCLearn): A Student Perspective - Zulu, Remaketse Francis (The IIE, 2020)
The problem identified for this research is that private education provider’s students are not using an LMS effectively, not completing their activities and not engaging fully with the system. The problem was identified by analysing the students’ LMS usage reports of the academic year 2019. Furthermore, lecturers whose students were not completing activities on an LMS also pointed out the problem. The initial impressions suggested that there were two underlying problems, which were the poor usability of an LMS and that students did not see the value of engaging on an LMS. However, for this study, the researcher only focused on the usability of an LMS. The study followed a qualitative approach and because of lockdown, the data was collected making use of Microsoft Forms of which the link was shared with the study participants. The study consisted of 87 participants who voluntarily took part in the study. The findings of the study revealed that LMS is important for enhancing teaching and learning. Furthermore, for the most part, majority of the students were satisfied with the private education provider’s LMS, indicating that LMS is useful in teaching and learning. However, only a few students experienced technical issues and they also pointed out that LMS used requires more improvements.
Keywords: Enhancing Teaching and Learning; Learning Management Systems; LMS; LMS effectiveness